Magnetic resonance imaging safety in nonconditional pacemaker and defibrillator recipients: A meta-analysis and systematic review - Shah, Anand D.; Morris, Mike A.; Hirsh, David S.; Warnock, Megan; Huang, Yijian; Mollerus, Michael; Merchant, Faisal M.; Patel, Anshul M.; Delurgio, David B.; Patel, Adarsh U.; Hoskins, Michael H.; El Chami, Mikhael F.; et al. (Heart rhythm, 2018)
Recommendations regarding performance of magnetic resonance imaging (MRI) in non-MRI conditional pacemaker and defibrillator recipients are evolving. Previous studies have suggested low adverse event rates with MRI in nonconditional cardiac implantable electronic device (CIED) recipients, but low power limits optimal characterization of risk. The purpose of this study was to perform a systematic review and meta-analysis to characterize the clinical risk associated with MRI in CIED recipients in order to improve power. PubMed and CINAHL indexed articles from 1990 to 2017 were queried. A random effects model was used for meta-analysis of continuous variables. Safety outcomes were evaluated with descriptive statistics. Seventy studies of non-MRI conditional devices undergoing MRI were identified, allowing for analysis of 5099 patients who underwent a total of 5908 MRI studies. Heterogeneity in lead parameter changes was observed within studies, although smaller variances were noted between studies. All lead characteristics and battery voltages showed very small, clinically insignificant changes when assessed as a pooled cohort, although cases of clinically relevant outcomes were also noted (lead failure 3, implantable cardioverter–defibrillator shock 1, electrical reset 94). Electrical resets were found only in older devices. Defibrillator function was unchanged, and inappropriate shocks were avoided with pre-MRI programming changes. This review demonstrated low lead failure and clinical event rates in non-MRI conditional pacemaker and defibrillator recipients undergoing MRI. Observed changes were small and interstudy variance was low, suggesting that the composite event rates offer a reasonable estimate of true effect. The observed adverse events reinforce the need for ongoing vigilance and caution, particularly with older devices.